Federalism in Canada evolving constitutional, political, and social realities - Brock, Kathy L. 1958-; Hale, Geoffrey E. 1955- (Irwin Law, 2023)
"What does the concept of "federalism" mean and how does a federation differ from a unitary state? Professors Brock and Hale focus specifically on Canada as an example of a federal state and explain both the characteristics of Canadian federalism and the evolution of the practice of federalism in the decades since "Confederation." Federalism is not exclusively a legal doctrine. It is a method for the conduct of public affairs that combines a constitutional-legal framework with flexible public administration methodologies. It is a method of governing that naturally incorporates practicality and mutual accommodation among layers of government. It is a vehicle of public life that generates its own controversies, difficulties, and indeed, sometimes crises, all of which require resolution through that very methodology of federalism. Professors Brock and Hale explore the most fundamental aspects of, and practices in, the Canadian form of federalism and go on to enlighten all readers about a variety of aspects of this form of government."
"Institute of Parliamentary and Political Law / Institut de droit parlementaire et politique"
Keywords: Föderalismus; Kanada; Federal government / Canada; Canada / Politics and government; Canada / Politique et gouvernement; Federal government; Politics and government; Canada / https://id.oclc.org/worldcat/entity/E39PBJkMHVW4rfVXPrhVP4VwG3